Exosome: a novel mediator in drug resistance of cancer cells. (12th October 2018) - Zhang, He-da; Jiang, Lin-Hong; Hou, Jun-Chen; Zhong, Shan-Liang; Zhu, Ling-Ping; Wang, Dan-Dan; Zhou, Si-Ying; Yang, Su-Jin; Wang, Jin-Yan; Zhang, Qian; Xu, Han-Zi; Zhao, Jian-Hua; et al.
Exosomes are small membrane vesicles with a diameter of 40–100 nm, which are released into the intracellular environment. Exosomes could influence the genetic and epigenetic changes of receptor cells by promoting the horizontal transfer of various proteins or RNAs, especially miRNAs. Moreover, exosomes also play an important role in tumor microenvironment. Exosomes could promote the short- and long-distance exchanges of genetic information by acting as mediators of cell-to-cell communication. In addition, exosomes participate in drug resistance of tumor cells by genetic exchange between cells. It is reported that exosomes could be absorbed by recipient cells and transmit chemoresistance from drug-resistant tumor cells to sensitive ones. Then understanding the mechanisms of chemotherapy failure and controlling tumor progression effectively will be a major challenge for us. Therefore, in this review, we will briefly reveal the role of exosomes in drug resistance.